Programs' efficacy to develop employable skills for people with functional diversity: A meta-analysis - Carolina Gonzálvez; Fernando Marhuenda-Fluixá (International Journal for Research in Vocational Education and Training (IJRVET), 2021)
Purpose: Promoting the labour integration of people with functional diversity is a key element to achieve their social inclusion. This meta-analysis aims to examine the effectiveness of experimental programs in developing employable skills for people with disabilities. Methods: Literature searches up to June 2019 were conducted in four databases (Web of Science, Scopus, PsycINFO and ERIC). Studies that met the following criteria were selected: (1) The program should develop employable skills; (2) the participants should be people with functional diversity; (3) the study should have a design with an experimental group and a control group as well as pretest and posttest measurements; (4) the study had to provide enough data to calculate the effect sizes; and (5) the study had to be written in English or Spanish. 67 independent studies met the selection criteria, among 14 articles published between 1998 and 2019. Results: The results revealed mean effect sizes in favour of the experimental group for the set of all studies according to data reported by people with functional diversity, as well as according their relatives and teachers. The two dimensions of the programs with a significant effect size in favour of the experimental group were interview skills and career planning. Furthermore, it was found that the programs showed a higher degree of effectiveness in groups formed only by people with intellectual disabilities, with a lower educational level, whose duration ranged from six to twelve months. This was particularly the case with participants from Spain and Australia. Conclusion: Promoting the labour insertion of people with disability is a key element to achieve their social inclusion. Programs that support and develop employability and that are conducted upon experimental conditions do have a positive impact upon young people with functional diversity. Upon the results, we discuss practical implications for integrating disabled persons into the labour market.
Keywords: 330; Employability; Transition From Education and Training to Employment; People With Disability; Career Planning; Vocational Education and Training; VET